Aquatic invasive species: the economic cost-benefit balance of human-made infrastructure - Boltovskoy, Demetrio (2022)
Human-made facilities and major constructionprojects, like navigation canals and water-transfer canalsand pipelines, can facilitate the spread of aquatic alienspecies, some of which may have negative impacts on thehabitats invaded, and on the economy. However, thepositive economic impacts of such facilities are usuallymuch higher than their costs, and their ecosystem-servicevalues are usually mixed, with both positive and negativeecological impacts being common.